2014
DOI: 10.18632/oncotarget.1795
|View full text |Cite|
|
Sign up to set email alerts
|

Functional analysis of MKP-1 and MKP-2 in breast cancer tamoxifen sensitivity

Abstract: Increased activation of ERK signaling has been reported in breast cancer models of acquired tamoxifen resistance. Here, we examined the expression of Mitogen-Activated Protein Kinase Phosphatases (MKPs) 1 and 2 following tamoxifen treatment and the effects of MKP-1/MKP-2 overexpression on tamoxifen sensitivity. Treatment of MCF7 breast cancer cells with tamoxifen increased MKP-2, but not MKP-1, protein levels. Overexpression of MKP-1 or MKP-2 inhibited estrogen-induced MCF7 cell proliferation compared to vecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…(iii) As bispecific protein phosphatases, MKP proteins can inactivate the phosphorylated MAPK through dephosphorylation at residues Ser and Tyr of TXY motif. Among them, MKP1 and MKP2 can dephosphorylate ERK, JNK, and p38, which negatively regulated MAPK cascades (55). Phosphorylation at residues Ser359 and Ser364 in MKP1 by ERK1 and ERK2 enhanced MKP1 stability and protected it from proteasome-mediated degradation (56).…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…(iii) As bispecific protein phosphatases, MKP proteins can inactivate the phosphorylated MAPK through dephosphorylation at residues Ser and Tyr of TXY motif. Among them, MKP1 and MKP2 can dephosphorylate ERK, JNK, and p38, which negatively regulated MAPK cascades (55). Phosphorylation at residues Ser359 and Ser364 in MKP1 by ERK1 and ERK2 enhanced MKP1 stability and protected it from proteasome-mediated degradation (56).…”
Section: Mapk Pathways Were Dysregulated In Nfpasmentioning
confidence: 99%
“…MKP-1, the first defined member of MKPs [8], has been regarded as an important regulator of innate immune response and tumorigenesis by deactivating both MAP kinases and NFκB pathway in immune cells [915]. Previous study has shown that MKP-1 transcripts are detected in E14.5 mouse embryonic reproductive system by RNA in situ hybridization [16].…”
Section: Introductionmentioning
confidence: 99%
“…By changing the phosphorylation site of RAF1, appl1 activates the mapk/erk cell-signal pathway 29 . The mapk/erk pathway promotes tumour cell proliferation and suppresses tumour cell apoptosis 30 . The mapk/erk pathway activates many oncogenes-for example, COX2 31 .…”
Section: Discussionmentioning
confidence: 99%